EFFECT OF VITAMIN E AND SELENIUM INJECTION ON SOME PHYSIOLOGICAL CHARACTERISTICS AND BIOCHEMICAL PARAMETERS IN LOCAL RAM LAMB - HASAN, WARVEEN I.; MUSTAFA, KAMAL N. S. (Journal of Duhok University, 2020)
The aim of present study was to investigate the response of vitamin E and selenium injection in local ram lambs on the hematological aspect, thyroid hormones, biochemical parameters, and growth rate. Twenty-four weaned (3-4 month old) ram lambs and averaged 20.827±0.5 kg in weight were used. The lambs were divided randomly into three groups (8 lambs each). 1st group was served as the control, the lambs were injected with 1.0 mlof physiological saline solution (0.9%), 2nd group (T1), lambs were injected intramuscularly with vitamin E 2.5 mg/kg of body weight and sodium selenite 25μg/kg of body weight and 3rd group (T2), the lambs were injected intramuscularly with vitamin E 5 mg/kg of body weight and sodium selenite 50μg/kg of body weight. The injection administered at weekly interval for 12 weeks. Results showed that T1 significantly increased packed cell volume (PCV %) and lymphocytes. The result of current study did not show a significant change between the test group in growth rate, ESR, thyroid hormones, biochemical parameter including (glucose, total protein, albumin, globulin, cholesterol, and triglyceride and aspartate aminotransferase).In conclusion, injection of vitamin E and selenium has positive effect on some physiological parameters in local ram lamb.